Use of cancellous bone grafting to promote granulation tissue in a distal limb wound in a dog. (7th May 2018) - Barnes, K.; Lanz, O.; Barry, S.; Aulakh, K.
Abstract : A 5‐year‐old female spayed Shetland sheepdog presented for evaluation of bandage sores on the left pelvic limb after a splint was placed to stabilise a digit fracture incurred approximately 2 weeks previously. Multiple areas of necrosis were identified upon bandage removal. After debridement of devitalised tissue, a 4 cm wound on the plantar surface of the metatarsal bones (with exposed bone and tendons) remained. The Papineau technique (which involves removal of infected or necrotic tissue, placement of autogenous cancellous bone graft within a wound, and delayed skin closure) was used to treat this wound. Use of bone graft in this manner aims to promote early granulation tissue formation and reduce the time until wound reconstruction can be performed. Autogenous cancellous bone graft was harvested from the proximal humerus and placed within the metatarsal wound. Once a healthy granulation tissue bed was noted to cover the bone graft, a meshed full thickness skin graft was placed. To our knowledge, this is the first report of the Papineau technique being used for this purpose in a dog.